Literature Review: Motor Analysis of Deaf Children - Antoni, Rizka; Muhammad Furqon Hidayatullah; Slamet Riyadi; Bramastia (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This article provides an empirical review of deaf children. The purpose of this article is to analyze the motor skills of deaf children. This type of research is a literature review where researchers will explore and analyze a number of scientific data taken from Google schoolar stored in Publish or Perish software. The keyword used is deaf children's motor skills. There were a total of 7 articles about deaf children's motor skills. 5 studies explained that gross and fine motor learning can improve deaf children's motor skills, such as fan dancing, Malay dance, sewing, game-based motor learning models in PE learning and independence training models. 2 of the studies discussed the gross motor skills of SLB children in the good category. Based on the results of the literature review, it can be concluded that many activities can be used as a reference to improve the motor skills of deaf children, fine motor and gross motor. The 7 articles prove that all treatments used in the study can generally increase the motor skills of deaf children. Children's motor development will be different for each individual. This is where the task of parents or teachers to train children's motor skills to always develop in various ways. It can be with art or physical activity and exercise.